Clonazepam as Agonist Substitution Treatment for Benzodiazepine Dependence: A Case Report - Angelo Giovanni Icro Maremmani; Luca Rovai; Fabio Rugani; Silvia Bacciardi; Matteo Pacini; Liliana Dell'Osso; Icro Maremmani (Case Reports in Psychiatry)
Nowadays, the misuse of benzodiazepines (BZDs) is a cause for a serious concern among pharmacologically inexperienced patients, whether treated or untreated, that could lead to significant complications, including tolerance, dependence, and addiction. We present a case report in which an Italian patient affected by anxiety disorder and treated with BZDs presented a severe case of dependence on BZDs. We treated him according to an agonist substitution approach, switching from the abused BZD to a slow-onset, long-acting, high potency agonist (clonazepam), and looking at the methadone treatment model as paradigm. We decided to use clonazepam for its pharmacokinetic properties. The advantage of choosing a slow-onset, long-lasting BZD for the treatment of our patient was that it led us to a remarkable improvement in the clinical situation, including the cessation of craving, absence of withdrawal symptoms, reduced anxiety, improvements in social functioning, and a better cognition level.